Actividad práctica de genética de poblaciones para alumnos de C.O.U. - Conde Domingo, G. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
Starting from two populations with identical genic frequencies, one of them being balanced and the other unbalanced, and being their genes represented by «pieces of paper)) that may be taken out at random from a box or bag, we sha!l obtain the same genotypic frequencies in both of them, coinciding with those of the balanced population. Students must deduce the necessary conditions for equilibrium in a population by comparing the different genic and genotypic frequencies of both original populations with the populations resulting from this experiment.